Adobe InDesign CC classroom in a book (2014 release) : the official training workbook from Adobe - Anton, Kelly Kordes (Classroom in a book., 2015)
The fastest, easiest, most comprehensive way to learn Adobe InDesign CC (2014 release) Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does--an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe InDesign CC Classroom in a Book contains 16 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. In addition to learning the key elements of the InDesign interface, this completely revised CC (2014 release) edition covers new features, including rows and columns in tables, dual PDF and IDML file packaging, fixed and reflow EPUBs, and major improvements in the way text and graphics are handled during EPUB export. Purchasing this book gives you access to the downloadable lesson files you need to work through the projects in the book, and to electronic book updates covering new features that Adobe releases for Creative Cloud customers. For access, goto www.peachpit.com/redeem and redeem the unique code provided inside this book. "The Classroom in a Book series is by far the best training material on the market. Everything you need to master the software is included: clear explanations of each lesson, step-by-step instructions, and the project files for the students." Barbara Binder, Adobe Certified Instructor Rocky Mountain Training